Use of Forecasting Methods in Price Analyses - Balogh, Péter (Acta Agraria Debreceniensis, 2003)
The cost of products changes not only seasonally in relation to time, but also follows a hectic motion. It is necessary for the farmers to calculate in advance the size of the future income, which is one of the basic conditions of the economical production. Many authors have examined the change of the prices but since the tendency of the change of the prices can be only rarely observed purely by itself, therefore it is difficult to separate it. During my research I examined how the monthly prices of corn and the monthly buying prices of pigs for slaughter have changed since 1991 and how much their future value will be. I examined how much is the α factor wich gives the minimal residual variation in case of the Brownian dual exponential smoothing and the corrected dual exponential smoothing and how will the future (2002) prices, which were in this way calculated, change compared to their real market prices.